Assessing the Discourse System and the Visual Utterance System in the Artworks of Committed Iranian Paintings in the 60s and 70s - Zabolinezhad, Hoda; Qazvini, Parisa Shad (Journal of Ecohumanism, 2024)
An attempt is made to answer the questions: How to base the Utterance system in the visual texts of Iranian painting, based on commitment discourse theory in the literature of the 60s and 70s? and What is the main difference between the Utterance and Discourse systems in visual arts? The generating institutions of this type of Utterance system necessitate the referential function for visual texts as the main component in the formation of such texts. According to these institutions, production of artwork as classical and ornamented texts convey only one meaning, unlike the phenomenal texts with multiple meanings, next to illustrating how some outstanding and common semantic signs lead to the formation of this type of Utterance system in the Iranian art.